Molecular methods for identification and characterization of novel papillomaviruses. (September 2015) - Kocjan, B.J.; Bzhalava, D.; Forslund, O.; Dillner, J.; Poljak, M.
Abstract: Papillomaviruses (PV) are a remarkably heterogeneous family of small DNA viruses that infect a wide variety of vertebrate species and are aetiologically linked with the development of various neoplastic changes of the skin and mucosal epithelia. Based on nucleotide similarity, PVs are hierarchically classified into genera, species and types. Novel human PV (HPV) types are given a unique number only after the whole genome has been cloned and deposited with the International HPV Reference Center. As of 9 March 2015, 200 different HPV types, belonging to 49 species, had been recognized by the International HPV Reference Center. In addition, 131 animal PV types identified from 66 different animal species exist. Recent advances in molecular techniques have resulted in an explosive increase in the identification of novel HPV types and novel subgenomic HPV sequences in the last few years. Among PV genera, the γ-PV genus has been growing most rapidly in recent years with 80 completely sequenced HPV types, followed by α-PV and β-PV genera that have 65 and 51 recognized HPV types, respectively. We reviewed in detail the contemporary molecular methods most often used for identification and characterization of novel PV types, including PCR, rolling circle amplification and next-generation sequencing. Furthermore, we present a short overview of 12 and 10 novel HPV types recently identified in Sweden and Slovenia, respectively. Finally, an update on the International Human Papillomavirus Reference Center is provided.